ANALYSIS OF THE ECOLOGICAL AND ECONOMIC SITUATION IN THE NATIONAL ECONOMY OF THE REPUBLIC OF DAGESTAN - A. G. Abdurakhmanova; A. M. Shakhbanovа (Юг России: экология, развитие, 2017)
Aim. The article is devoted to consideration of issues of priority development of regions and transition to sustainable development from the point of view of international law. Great attention is paid to the analysis of priority development regions and the right to sustainable development. It is proposed to develop model of formation of priority development regions in the context of sustainable economic development the conclusions about the validity of consideration of cultural diversity as the fourth dimension of sustainable development.Methods. We used the following methods: historical and comparative analysis, system approach, analysis of the statistical and mathematical materials.Results. A model of the formation of priority development regions in the context of sustainable economic development, which defines the purpose and objectives of social reporting, legal and regulatory framework for its formation, principles and basic models for determining measures of social responsibility, explored the most promising industry in the region with the economic-geographical point of view.Conclusion. We identified socio-economic problems of sustainable development of the Republic of Dagestan and also offered important directions for sustainable development in the region.